Altitude training for sea-level competition - Baker, A.; Hopkins, W. (Sportscience, 1998)
Summary: Training near sea level while living at an altitude of 2500 m (8000 ft) for a month enhances subsequent endurance performance, probably by increasing the oxygen-carrying capacity of the blood through an increase in production of red blood cells. A small proportion of athletes shows no improvement or even reduced performance with this "live-high train-low" strategy, but the enhancement for the average athlete is 2-3%. The extra red blood cells and the enhancement of performance are probably lost by 2-3 months after return from altitude. Living and training at altitude is less effective than living at altitude and training near sea level, because the lack of oxygen at altitude results in detraining through reduction in intensity of training. Loss of heat acclimatization from training in cooler temperatures at altitude can also reduce the benefit of altitude exposure. Sprinters may benefit from living or training at altitude, but less is known about the magnitude, duration, and mechanism of the effect. Athletes residing at altitude can get the benefit of training at sea level by performing high-intensity training on ergometers while breathing oxygen-enriched air. Athletes residing at sea level can simulate altitude exposure by resting in a chamber at reduced air pressure or in a "nitrogen house" or tent flushed with air containing less oxygen. Infusions of blood or injections of the hormone erythropoietin also simulate effects of altitude exposure. All of these practices can increase the fraction of red cells in the blood toward a dangerous level, so they need to be monitored and controlled by blood testing.